Interfacial arrangement and phase transitions of PNiPAm microgels with different crosslinking densities - Rey, Marcel; Hou, Xunan; Tang, Jo Sing; Vogel, Nicolas (Soft Matter, 2017)
Microgels are colloidal hydrogel particles that exhibit a pronounced softness, which arises from the swollen nature of the constituent polymer network. This softness leads to a substantial deformability of such particles at liquid interfaces, which, in turn translates into a complex phase behaviour that can exhibit a phase transition between a non-close packed and a close packed arrangement. Here, we explore how the degree of swellability and deformability - and therefore the softness of the particles - affects the phase behaviour of microgels at the air/water interface upon compression. We use precipitation polymerization to synthesize poly(N-isopropylacrylamide) microgels with similar hydrodynamic radii in the collapsed state and systematically vary the degree of swellability by changing the crosslinking density. We spread these microgels onto the air/water interface of a Langmuir trough and characterize their interfacial properties by surface pressure - area isotherms. Furthermore, we continuously transfer the interfacial microgel monolayer during compression onto a solid substrate, thus encoding the complete phase diagram of the microgels with increasing particle density as a function of the position on the solid substrate. We investigate the microgel arrangement by atomic force microscopy and scanning electron microscopy and use image analysis to extract quantitative information on the interparticle distance and degree of order. We find that the phase transition is very sensitive to the crosslinking density and occurs at much lower surface pressures for less deformable particles. The softest microgels do not undergo any phase transition. Instead, the system exhibits pronounced local conformation changes around point defects with local five- and sevenfold symmetries, indicating that the geometry of the assembled structure effectively controls the local pressure experienced by the microgels.